A novel Zn(II) coordination polymer based on tetra-carboxylates ligand and N-donor ligand: synthesis, structure and photocatalytic properties. (24th May 2018) - Wang, Shu-Long; Huang, Wen-Fang; Wei, Qing-Min; Chen, Zhi-Lin; Tan, Ming-Xiong
Abstract: A new Zn(II) coordination polymer, namely, [Zn(pbta)0.5 (bpa)]·2H2 O (1 ) [H4 pbta = 5, 5′-phenylenebis(methylene)-1, 1′-3, 3′-(benzene-tetra-carboxyl c acid, bpa = 1, 2-bis- (4-pyridyl)ethane]. The complex1 has been synthesized under hydrothermal conditions and characterized by elemental analysis, infrared spectra (IR), thermogravimetric analysis, UV-vis spectra, powder X-ray diffraction and X-ray single crystal diffraction. The complex1 is formed by stacking of the 2D windows, and the 3-fold interpenetrated 3D network by hydrogen bonds between the coordinated water molecules and adjacent carboxylate oxygen atoms. In addition, the photocatalytic activities of complex1 for decomposition of methylene blue (MB) under UV light have been investigated.